SEX DIFFERENCES IN OCCIPITAL CONDYLES IN MAIDUGURI, NORTHEASTERN NIGERIA USING COMPUTED TOMOGRAPHIC SCAN IMAGES - Zirahei JV; Amaza DS; Otashu KF; Nkimanya F; Gadzama NM; Mailabari HY (Ntec Specialist, 2018)
Background: Measurements of the occipital condyle (OC) have been reported to be used in sex identification. Hence, the present study attempts to find out whether the OC is sexually dimorphic, and whether morphometric analysis of the same, using computed tomography (CT) scan images, could be a useful tool in sex determination in the sample population. Method: The sample population comprised of basicranial CT images of 110 patients (60 males and 50 females) aged 18-65 years obtained from the Federal Neuropsychiatric Hospital, Maiduguri, Borno State Nigeria. The parameters measured were the right and left antero-posterior and mid-transverse distances of the OC. Results: Males have significantly higher mean values for all the OC parameters measured (p less than 0.001). The success rate for sex identification using Baudoin condylar index (BCI) was 52.92% for males and 46.67% for females. On deploying demarking points (DPs) for sex determination, however, only 13 (21.67%) out of the 60 males were identified using right antero-posterior distance of the OC and 7 (11.67%) using right mid-transverse distance. Using right mid-transverse distance, 8 (16%) of the 50 females were identified and 6 (12%) of the 50 females were identified using left mid-transverse distance. Conclusion: This study showed that the OC is sexually dimorphic and can be used in sex determination in the sample population. Although the occipital condyles can be used in sex estimation, they remain, however, inadequate for forensic application especially when demarking points and Baudoin condylar index are the methods to be deployed for this purpose